GAMBARAN HISTOPATOLOGI LIMPA MENCIT (Mus musculus Balb/C) YANG DIINFEKSI DENGAN Plasmodium berghei - Intania Dwiputri Hendriani (Majalah Kedokteran Andalas, 2024)
Objective: to determine the histopathological picture of the spleen of mice (Mus musculus Balb/C) infected with Plasmodium berghei which has been immunized with An. sundaicus salivary gland extract. Method: This type of research is a descriptive study with a quantitative approach. This research was conducted at the Histology Laboratory of the Faculty of Medicine, Andalas University, from March 2023 to September 2024. Result: research on the histopathological picture of the spleen of mice Mus musculus Balb / C infected with Plasmodium berghei showed the number of spleen cell megakaryocytes in the control group with an average of 2.63 per field of view, in the pellet extract group 2.23 per field of view and in the supernatant extract group 2.13 per field of view. Conclusion: the average megakaryocyte cells in the spleen were the highest in mice injected with the control group and the average megakaryocyte cells in the spleen were the lowest in mice injected with the supernatant extract group.